GEOMETRY OF HOLOCENE TIDAL NOTCHES – SEA LEVEL MARKERS AT PERACHORA PENINSULA, GULF OF CORINTH, GREECE - Schneiderwind, S.; Kázmér, M.; Boulton, S.; Papanikolaou, I.; Reicherter, K. (Bulletin of the Geological Society of Greece, 2016)
Tidal notches are a generally accepted sea level indicator that, when different from mean sea level, witness tectonic activity at or near coastlines. However, how to infer related information is controversial since tectonic uplift from a single seismic event is not likely to exceed several decimetres. High resolution laser scanning offers the availability of close-up views on exposures and to detect evidence for multiple sea level indicators in between major emergence. Statistically representative profiles along exposure were analysed in order to prove for already described tidal notches and to highlight similar shapes in consistent geometries along coastal cliffs of Perachora Peninsula.